Analytic Determination of Reference Passenger Car Size for Parking Space Dimensioning in Croatia - Brčić, Davor; Šoštarić, Marko; Ševrović, Marko (Promet - Traffic&Transportation, 2012)
Dimensions of parking spaces have been subject to standardization in recent decades in the world. Different state institutions and standardization committees regulated parking space sizes based on typical passenger car size and ergonomic conditions. Most of these regulations are not following the notable growth in size of passenger cars that has been the case in the past 30 years. In that period in Croatia, a significant increase was also observed in the number of passenger cars in mid-sized and large passenger car classes thus emphasising the problem of outdated and inadequate parking space dimension standard. In this paper an analytic procedure is presented that takes into account the number and types of passenger cars registered in Croatia that leads to the determination of reference passenger car size. This reference values, as well as other relevant ergonomic standards are used to calculate the recommended parking space dimensions in Croatia. The purpose of this analysis is to produce new recommendations and suggest new design standards for parking spaces in Croatia as well as to provide analytic procedures to conduct similar researches in other areas.